Teaching history with musicals - Edney, Kathryn, 1972- (Teaching history with ..., 2017)
This volume serves as a guide for teaching history with musicals. In addition to covering key themes and concepts, this book provides an overview of significant issues and related musical theatre and film productions, a tutorial in critique, user guides for resources, a model syllabus, and sample exercises and assignments for classroom use.